Tissue plasminogen activator and neuroserpin are widely expressed in the human central nervous system - Teesalu, Tambet; Kulla, Andres; Simisker, Aadu; Sirén, Vappu; Lawrence, Daniel A.; Asser, Toomas; Vaheri, Antti (Thrombosis and Haemostasis, 2004)
Tissue plasminogen activator (tPA) is increasingly recognized to play important roles in various physiological and pathological processes in the central nervous system (CNS). Much of the data on the involvement of plasminogen activators in neurophysiology and -pathology have been derived from studies on experimental animals. We have now performed a systematic characterization of the expression of tPA and its inhibitor, neuroserpin, in normal human CNS. Brain and spinal cord samples from 30-36 anatomic locations covering all major brain regions were collected at 9 autopsies of donors with no neurological disease. Tissues were embedded in paraffin and tissue arrays were constructed. In two cases parallel samples were snap-frozen for biochemical analysis. Expression and activity profiling of tPA and neuroserpin were performed by immunohistochemistry, in situ hybridization, immunocapture and zymography assays. In the adult CNS, tPA was expressed at the mRNA and protein levels in many types of neurons, in particular in thalamus, cortex of cerebellum, pontine nuclei, neocortex, limbic system, and medulla oblongata. Interestingly, tPA was often co-expressed with its CNS inhibitor, neuroserpin. Despite overlapping expression of tPA and neuroserpin, zymography and immunocapture assays demonstrated that human neural tissue is a rich source of active tPA. Our analysis documents a detailed map of expression of tPA and its inhibitor in the human CNS and is compatible with the view that tPA is a key player in CNS physiology and pathology.
Keywords: Tissue plasminogen activator; neuroserpin; human central nervous system; neuron; tissue array